Exploring aspects of Community of Inquiry (CoI) in Afrophilia learning processes for transformative education using an Afrophilic 'Philosophy for Children' approach: a case of Sebakwe resettlement primary schools in the Midlands Province of Zimbabwe - Bhurekeni, John (Rhodes University, Faculty of Education, Department of Education)
This study focused on investigating and developing an Afrophilic orientation to a sociocultural approach to philosophy for children. The main aim was to foster a critical and generative approach to considering the heritage-based curriculum foundations of Zimbabwean primary schools, focusing on Sebakwe resettlement primary schools (the case study area). Afrophilia foundations in the study are regarded as "the discourses that are the medium of philosophical reflexion" (Rettova, 2004, p. 4) in each African society. As articulated in the study, such discourses include African proverbs, poems, stories, music, and folktales which are useful in the initiation of philosophical engagements with children in a community of inquiry approach. A community of inquiry is a framework that reflects a collaborative-dialogical approach to teaching and learning. Curriculum reviews in postcolonial Zimbabwe have revealed an unconscious misalignment of the Zimbabwean education system's philosophical underpinnings because it has continued to align itself with imperial British colonial philosophy, which contradicts the country's developmental needs (Presidential Commission of Inquiry into Education and Training [CIET], 1999, Zimbabwe Ministry of Primary and Secondary Education [MoPSE], 2014). The philosophical misalignment is an extension of the colonial history of Zimbabwe showing that vestiges of colonial rule still shape the education sector. This leaves the education system focusing mainly on abstracted concepts with continued marginalisation of local cultures, discourses, and knowledge. Consequently, it leaves Zimbabwe together with other postcolonial education systems with the task of dealing with the phenomenon of colonial continuity. One implication of these colonial continuities, is learner disinterest in learning, which affects the educational process negatively, affecting the learning of critical reflexive thinking, an issue which I have observed in the Sebakwe resettlement schools involved in this study where I have been teaching for 15 years. To address, this, the study sought to answer the following questions: What historical and contemporary barriers are affecting the promotion of a culture of learning in Zimbabwean resettlement primary schools, particularly as they relate to learners' underdevelopment of critical reflexive thinking skills? In addition, How can the Philosophy for Children Afrophilia curriculum intervention promote a culture of learning in Sebakwe resettlement primary schools that is oriented toward the development of critical reflexive thinking skills in children? In approaching the research questions, I applied postcolonial and decolonisation theory, sociocultural learning theory and curriculum theory aimed at transformative change, that is oriented towards achieving a more contextually oriented approach to teaching and learning, and a paradigm of 'learning as connection' (Lotz-Sisitka & Lupele, 2017; Shumba, 2017). This has been identified as a 'missing' discourse in mainstream educational quality discourses in southern Africa (Lotz-Sisitka & Lupele, 2017). Furthermore, to create space for curriculum development using multi-actor groups in a community of inquiry, I used decolonial research methodologies in the data generation process. The study is constituted as an interventionist case study, and I applied a four-stage process comprising document analysis, workshops, participant observations involving children between 8-11 years, and reflective interviews with parents, educators and children as instruments for data gathering. I also used process-based analytical tools developed in Philosophy of Children research to analyse the processes of critical reflexive thinking development that emerged from the Philosophy for Children pedagogy involving ten lessons which I facilitated, and videorecorded. Moreover, I used postcolonial and decolonial discourse analysis to provide the broader analytical insights that informed the interpretations of the lesson analysis data from the perspective of the research problem that I address across the research project. This PhD is produced as a PhD by publication, which involves publishing of papers, and orientation to, and interpretation of the papers. The main findings of this study are reported in articles that I prepared for publication, three of which have already been published (see Appendices A1, A4 and A5), and four which have been submitted for publication (A2, A3, A6, A7) with some already at an advanced stage of finalisation via review. The conceptual paper (A1) that served as the foundation for the publication journey revealed that, in addition to the weight of cultural technologies of domination, the curriculum is shaped by the paradox of a superficial interpretation of unhu/ubuntu educational philosophy. As a result, the curriculum becomes disconnected from the learners' real-world experiences. The second paper (A2), which focuses on why Zimbabwe needs the Philosophy for Children approach with a sociocultural medley, unveils Zimbabwe's complex decolonial curriculum reforms and their many contradictions and paradoxes. However, it also emerged that the approach used in this study empowers teachers, is relevant to the emerging constellation of practices in the Sebakwe resettlement, and influences power sharing beyond teacher-child relationships. The third paper (A3), based on children's philosophy for children practice, defends the study's decision to bring children's heritage and cultural lens to bear on curriculum and pedagogical praxis. In essence, the article explores a synergy between philosophy for children and the Zimbabwean heritage-based educational curriculum, serving to enrich both. The fourth paper (A4) makes the case that philosophy for children could be a viable pedagogy for transformative education, and it provides evidence-based implementation of a context-based philosophy for children. According to this paper, the approach is effective in strengthening strong community relationships, instilling pride in local heritage, and advancing curriculum transformation. The fifth paper (A5) focusses on the approach's implications for teachers' roles, practices, and competencies. Six dimensions of teacher roles, practices, and competences surfaced, including the role of the teacher as a decoloniser and pedagogical innovator, among others. The sixth paper (A6), influenced by the previous papers' findings, focused on decolonisation and improving learning opportunities for children in the Sebakwe area using the philosophy for children approach. This paper's data depicts a 'third space' in which learners consolidate their cultural capital and curriculum content into their own meaning construction. The implication is that schools become neutral sites that improve learners' interdependence and inclusivity while also taking contextual realities into account. The findings of the seventh and final paper (A7) presented in this write-up advance the idea that a Philosophy for Children approach with a sociocultural medley influences an ethics of care by demonstrating how Afrophilia experiences influence a new path to wildlife conservation and sustainability. The study highlights that integrating Philosophy for Children and Afrophilia foundations of knowledge into the school curriculum promotes critical reflexive thinking skills, helps to address real-life problems and adds relevance to the curriculum. The study further shows that the integration of philosophy for children in the advancement of curriculum transformation in Zimbabwe is a successful formative interventionist approach in the resettlement schools that are characterised by a critical shortage of teaching and learning resources. In essence, the research opens an understanding that curriculum transformation and decolonisation are context-based and multi-actor processes, as showcased in the experiences of parents, teachers, education inspectors, and children in this study. Furthermore, this study posits that situating curriculum decolonization and transformation within unhu/ubuntu dialectical rationality and advancing diversity in reasoning necessitates deeper engagement with heritage-based curriculum and provides teachers with appropriate agency to modify and adapt their pedagogies in alignment with the learners' life world. According to the study, this emerged as a rational possible solution to the problem of curriculum decontextualisation. Curriculum decontextualisation as highlighted in the study via the problem of colonial continuity mentioned above, appears to be further influenced by the emphasis on examination assessment scores which seem to widen the gap between the adult and child worlds, as well as the gap between contextual realities and [curriculum] examination content. Overall, the study offers an approach that can deepen an unhu/ubuntu foundation for the heritage-based curriculum reform in Zimbabwe, and strengthen the learning of children in the resettlement schools, where the case was explored. Implications for further research are elaborated, as are possible implications for policy and practice.,Thesis (PhD) -- Faculty of Education, Education, 2023
Keywords: Culturally relevant pedagogy Zimbabwe; Curriculum change Zimbabwe; Philosophy-- Study and teaching (Elementary) Zimbabwe; Critical thinking; Decolonization Zimbabwe; Technology Political aspects; Representation (Philosophy)